Sistem Pendukung Keputusan Pemilihan Tanaman Obat untuk berbagai Macam Penyakit Menggunakan Metoda FUZZY di Toko Miswar Flora (Studi Kasus : Penyakit Demam) - Diantoro, Karno; Gustina, Dian (Jurnal Ilmiah FIFO, 2019)
Dengue Fever is a disease that often attacks the community. Sufferers of Dengue Fever are increasing every year. In this case natural treatments are still widely found drugs that can cure Dengue Fever and Typhoid Fever (tipes), to produce which medicinal plants are good, and examples according to Dengue Fever and Typhoid disease (typhus) still experience trouble. To overcome the selection of the right medicinal plants, a decision support system was created using Fuzzy Logic, Fuzzy Mamdani using Matlab system test aids. The method used in decision making is the fuzzy method. The method is because the fuzzy method can be used in making multi-criteria decisions and quite well in solving identification problems that require many criteria. On the results of testing existing data obtained data by comparison between data and processes in the matlab application, the valid level of application testing is 94.4%. Based on the results of the test carried out in this study, the Decision Support System is expected to help the community to determine the symptoms that arise so that it can be known about the fever between dengue fever and typhoid (typhus) so that the selection of medicinal plants is appropriate and can be used.